MR neurography in ulnar neuropathy as surrogate parameter for the presence of disseminated neuropathy - Bäumer, Philipp; Weiler, Markus; Rütters, Maurice; Heiland, Sabine; Bendszus, Martin; Pham, Mirko (PLOS ONE, 2012)
Purpose Patients with ulnar neuropathy of unclear etiology occasionally present with lesion extension from elbow to upper arm level on MRI. This study investigated whether MRI thereby distinguishes multifocal neuropathy from focal-compressive neuropathy at the elbow. Methods This prospective study was approved by the institutional ethics committee and written informed consent was obtained from all participants. 122 patients with ulnar mononeuropathy of undetermined localization and etiology by clinical and electrophysiological examination were assessed by MRI at upper arm and elbow level using T2-weighted fat-saturated sequences at 3T. Twenty-one patients were identified with proximal ulnar nerve lesions and evaluated for findings suggestive of disseminated neuropathy (i) subclinical lesions in other nerves, (ii) unfavorable outcome after previous decompressive elbow surgery, and (iii) subsequent diagnosis of inflammatory or other disseminated neuropathy. Two groups served as controls for quantitative analysis of nerve-to-muscle signal intensity ratios: 20 subjects with typical focal ulnar neuropathy at the elbow and 20 healthy subjects. Results In the group of 21 patients with proximal ulnar nerve lesion extension, T2-w ulnar nerve signal was significantly (p<0.001) higher at upper arm level than in both control groups. A cut-off value of 1.92 for maximum nerve-to-muscle signal intensity ratio was found to be sensitive (86%) and specific (100%) to discriminate this group. Ten patients (48%) exhibited additional T2-w lesions in the median and/or radial nerve. Another ten (48%) had previously undergone elbow surgery without satisfying outcome. Clinical follow-up was available in 15 (71%) and revealed definitive diagnoses of multifocal neuropathy of various etiologies in four patients. In another eight, diagnoses could not yet be considered definitive but were consistent with multifocal neuropathy. Conclusion Proximal ulnar nerve T2 lesions at upper arm level are detected by MRI and indicate the presence of a non-focal disseminated neuropathy instead of a focal compressive neuropathy.
Published November 14, 2012
Gesehen am 08.08.2018